(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The folate cycle is a cascade process of converting folic acid into a derivative available for absorption by the body, 5-methyltetrahydrofolate. The process is controlled by the enzyme methylenetetrahydrofolate reductase (MTHFR). Folate metabolism is a source of one-carbon fragments (methyl group -CH3) for vital cellular processes: purine nucleotide biosynthesis and conversion of uridine monophosphate into thymidylate; DNA and RNA methylation.